Methanogens, Methane and Gastrointestinal Motility - Triantafyllou, Konstantinos; Chang, Christopher; Pimentel, Mark (Journal of neurogastroenterology and motility, 2014)
Anaerobic fermentation of the undigested polysaccharide fraction of carbohydrates produces hydrogen in the intestine which is the substrate for methane production by intestinal methanogens. Hydrogen and methane are excreted in the flatus and in breath giving the opportunity to indirectly measure their production using breath testing. Although methane is detected in 30%-50% of the healthy adult population worldwide, its production has been epidemiologically and clinically associated with constipation related diseases, like constipation predominant irritable bowel syndrome and chronic constipation. While a causative relation is not proven yet, there is strong evidence from animal studies that methane delays intestinal transit, possibly acting as a neuromuscular transmitter. This evidence is further supported by the universal finding that methane production (measured by breath test) is associated with delayed transit time in clinical studies. There is also preliminary evidence that antibiotic reduction of methanogens (as evidenced by reduced methane production) predicts the clinical response in terms of symptomatic improvement in patients with constipation predominant irritable bowel syndrome. However, we have not identified yet the mechanism of action of methane on intestinal motility, and since methane production does not account for all constipation associated cases, there is need for high quality clinical trials to examine methane as a biomarker for the diagnosis or as a biomarker that predicts antibiotic treatment response in patients with constipation related disorders.